The Effect of Gelatin Concentration on the Characteristics of Nutmeg Jelly Candy (Myristica fragrans Houtt) - Tri P Lasmana; Helen C D Tuhumury; Erynola Moniharapon (Jurnal Agrosilvopasture-Tech, 2023)
Jelly candy is a confection composed primarily of sugar or blended with hydrocolloid components such as agar, gum, gelatin, starch, and carrageenan to make the product's texture moldable. The objective of this research was to determine the optimal gelatin concentration for nutmeg jelly candy quality. The present research employed Completely Randomized Experimental Design with one factor, namely the gelatin concentration, and three levels of concentration treatment: P1 = 20%, P2 = 30%, and P3 = 40%. The results indicated that a gelatin concentration of 30% was optimal for manufacturing nutmeg jelly candy with desirable physicochemical and sensory properties. Nutmeg jelly candy with 30% gelatin concentration had 35.0% moisture content, 0.21% ash content, 0.65% reducing sugar content before inversion, 23.11 kg/cm2 elasticity, and was preferred for taste, texture, and overall characteristics due to its nutmeg taste, slight nutmeg aroma, chewy texture, slight sweetness, and slight transparency